#TITLE_ALTERNATIVE# - (NIM : 12211019), MAHRURI
Electrical submersible pump or as known as ESP is one methods of artificial lift that be used in petroleum industry. The main problem that happen in field application of ESP well is gas interference. Gas which produced together with oil, can cause several problems such as cavitation, pump off, decreasing pump head, gas blocking, surging, slugging, and gas lock. Because of that, the methods to analize stability of ESP well is needed. Turpin Factor is one of the methods which can be used to analize ESP stability. Basically, this metthod calculate a constanta which is a function of pump intake pressure, gas flowrate, and liquid flowrate. If the value of constanta is, we can conlude that ESP in stable condition (any free gas not reduce pump performance). But if Turpin Factor is, , ESP in unstable condition. Firstly, Turpin Factor was proposed by Turpin et al at 1968 and correlation based on data of Lea and BeardenÃ‚Â’s experiment. In this final project will be discussed about how to know stability of ESP well based on Turpin Factor. This methods is very effective so we can decide are we have to install gas separator or not.